Invest in climate-smart soil and land health - Winowiecki, Leigh Ann; Mwongera, Caroline; Läderach, Peter R.D.; Acosta, Mariola; Ampaire, Edidah L.; Eitzinger, Anton; Lamanna, Christine; Mwungu, Chris Miyinzi; Shikuku, Kelvin Mashisia; Twyman, Jennifer (International Center for Tropical Agriculture, 2017)
Better soil health can increase agricultural productivity. Restoration activities can build on-farm resilience and contribute to climate change adaptation and mitigation.